Sanqi Oral Solution Ameliorates Renal Ischemia/Reperfusion Injury via Reducing Apoptosis and Enhancing Autophagy: Involvement of ERK/mTOR Pathways - Tian, Ruimin; Wang, Pinchao; Huang, Lihua; Li, Chuang; Lu, Zhaoyu; Lu, Zhisheng; Wu, Aijun; Bao, Kun; Mao, Wei; Huang, Qingming; Xu, Peng (Frontiers in Pharmacology, 2020)
Ischemia-reperfusion (I/R) induced acute kidney injury (AKI) is a significant health problem with high morbidity and mortality, yet prophylaxis strategies and effective drugs are limited. Sanqi oral solution (SQ) is a formulated medicine widely used in clinical settings to treat various renal diseases via enriching qi and activating blood circulation while its role on I/R-AKI remains unclear. Herein, by establishing rat I/R-AKI models, we intended to investigate the effect of SQ on prevention of I/R-AKI and explore its underlying mechanisms. We demonstrated that SQ treatment significantly attenuated renal dysfunction of I/R-AKI, alleviated histological damages, inhibited renal apoptosis and enhanced autophagy. Further investigation proved that SQ could significantly inhibit the activation of ERK and mTOR signaling pathways. Moreover, its renoprotective effect can be abolished by autophagy inhibitor 3-methyladenine (3-MA). Collectively, our results suggest that SQ exerts renoprotective effect on renal I/R injury via reducing apoptosis and enhancing autophagy, which are associated with regulating ERK/mTOR pathways.